The integration of Ki Hajar Dewantara's character education values into islamic education within the merdeka curriculum - Nanang Romadi; Muanif Ridwan; Qusthoniah Qusthoniah (Institute of Computer Science (IOCS), 2026)
Research on integrating Ki Hajar Dewantara’s character education values with Islamic education in the implementation of the Merdeka Curriculum remains limited. Character education is one of the primary focuses in the implementation of the Merdeka Curriculum as an effort to develop learners who are not only academically competent but also possess strong character aligned with the values of Pancasila. In this context, the educational philosophy of Ki Hajar Dewantara remains highly relevant, as it places character formation as the central objective of education. Likewise, Islamic education emphasizes the development of noble character (akhlaq) through the internalization of religious values in students’ daily lives. This study aims to analyze the integration of Ki Hajar Dewantara’s character education values into Islamic education within the Merdeka Curriculum and to identify their contribution to strengthening the Pancasila Student Profile. The study employed a qualitative approach using library research as its research design. Data were collected from various books, scholarly journal articles, policy documents, and relevant studies concerning character education, Islamic education, Ki Hajar Dewantara’s educational thought, and the Merdeka Curriculum. Data were analyzed using thematic analysis through the processes of identification, classification, interpretation, and synthesis of relevant literature. The findings indicate that Ki Hajar Dewantara’s character education values, including exemplary conduct, independence, mutual cooperation, wisdom, creativity, and respect for others, are strongly aligned with the values of Islamic education as well as the dimensions of the Pancasila Student Profile. The integration of these values can be implemented through classroom instruction, habituation practices, teacher role modeling, school culture, and collaboration among families, schools, and communities. The findings also reveal that integrating Ki Hajar Dewantara’s character education values into Islamic education can strengthen the implementation of the Merdeka Curriculum in fostering students who are faithful, morally upright, independent, creative, critical thinkers, and capable of living harmoniously in a diverse society. Therefore, the integration of Ki Hajar Dewantara’s character education values and Islamic education may serve as a relevant conceptual model for strengthening students’ character development in the contemporary educational era.